Pengaruh Disiplin Karyawan Terhadap Hasil Kerja Departemen Housekeeping Di The Reiz Suites Hotel Medan - Tambunan, Michael; Sebastiana, Sumihar; Yunita, Dina (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
The research method uses quantitative methods using validity tests, reliability tests, descriptive tests, simple linear regression analysis techniques,F tests, T tests. Data processing was carried out using SPSS (Statistical Package for Social Science) version 25.0 for windows. From the results of the study it is known that the effect of work discipline on the work of the housekeeping department at The Reiz Suites Hotel Medan, indicating that employee discipline (X) has no positive and significant effect on the work results of the Housekeeping Department employees (Y) can be calculated from the value of the Coefficient of Determination (R2 ) is equal to 0.025, which means that the influence of the independent variable on the dependent variable simultaneously is 0.25%, the remaining 97.5% is influenced by other causes not examined by the researcher.